2019
DOI: 10.18689/ijmr-1000103
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Synthesis of Hydroxy Apatite: Advantage and Application

Abstract: Production of nanostructured materials, similar to the complex structure of nanocalcite of hard tissues, egg shell, teeth and bone, are an attractive field of research. Calcium phosphates with clinical applications, such as hydroxyapatite (HA) (Ca 10 (PO4) 6 (OH) 2 ) have been widely used in regeneration of bone and fabrication of medical implants, mainly due to the chemical composition and structure similarity between HA and the mineral part of bones and teeth, and also as gene and drug delivery is used. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Regarding the effect of NHap on cell culture, this review showed that all studies had a positive effect on intervention groups, corroborating Hokmabad et al ( 6 ), who reported that the addition of NHap provides a suitable environment for cell proliferation and differentiation due to characteristics such as increased surface roughness, favoring the absorption of chemical species from the surrounding environment. Hydroxyapatite (HAp), Ca 10 (PO 4 ) 6 (OH) 2 , is one of the members of the apatite family, Ca 10 (PO 4 ) 6 (F,OH,Cl) 2 ( 4 , 17 ). Since it is the main mineral component of bones and teeth, synthetic HAp stands out in the field of material science for biological applications ( 5 , 13 , 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the effect of NHap on cell culture, this review showed that all studies had a positive effect on intervention groups, corroborating Hokmabad et al ( 6 ), who reported that the addition of NHap provides a suitable environment for cell proliferation and differentiation due to characteristics such as increased surface roughness, favoring the absorption of chemical species from the surrounding environment. Hydroxyapatite (HAp), Ca 10 (PO 4 ) 6 (OH) 2 , is one of the members of the apatite family, Ca 10 (PO 4 ) 6 (F,OH,Cl) 2 ( 4 , 17 ). Since it is the main mineral component of bones and teeth, synthetic HAp stands out in the field of material science for biological applications ( 5 , 13 , 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of nanoparticles to scaffolds has drawn attention of researchers as it favors conditions such as improved performance, increased adhesion rate, cell migration, proliferation, specific lineage differentiation, nutrient supply, and extracellular matrix deposition ( 3 - 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of chemical synthesis methods of HA(1,18,19).According to the findings of Hsieh et al, the sol-gel method has advantages over the other chemical methods listed in Table…”
mentioning
confidence: 99%